EFEKTIFITAS MEDIA DEKAK-DEKAK UNTUK MENINGKATKAN KEMAMPUAN MENGENAL NILAI TEMPAT BILANGAN BAGI ANAK BERKESULITAN BELAJAR MATEMATIKA - Dita Risfamelia (Universitas Negeri Padang, 2012)
This research background of the problems seen in the field, the children learning disability fourth grade in elementary 05 Kapalo Koto Pauh Padang who have difficulty in determining the place value of numbers. Under these conditions, the study aims to prove the effectiveness of media abacus in improving mngenal place value of numbers in mathematics learning for children in the fourth grade learning disability fourth grade in elementary 05 Kapalo Koto Pauh Padang. Abacus shaped like poles each pole contains beads.The research methodology used is a single subject research (SSR) is the A-B-A research design and analysis techniques visual graph. The results were analyzed included the number of observations in the baseline condition (A1) 10%, treatment condition (B) 90% the baseline condition (A2) 100%.